Effects of Some Breeding Criteria on Financial Evaluation Indicators for Dairy Cattle Investment Projects - Adnan Ünalan (Turkish Journal of Agriculture: Food Science and Technology, 2017)
This study was conducted with the aim of determining the probable effects of different real interest rates (RIR: 5, 6 and 7%), some key breeding criteria such as calving rate (CR: 80, 85 and 90%) and mean lactation milk yield per milking cow (MLML: 5000, 6000 and 7000 kg) on the financial evaluation indicators such as Benefit Cost Ratio (BCR) for a dairy cattle farm investment project taken as model, consisted of 100 heads of Holstein cows, which was established and operated during 20 years period in Turkey. In the study, firstly, current investment and annual operating costs for that kind of dairy cattle farm were determined according to optimal workmanship, housing, maintenance, feeding and health protection and then revenues were calculated from current sale prices of raw milk, slaughtered/breeding animal and manure. For each assumed different real interest rate, calving rate and mean lactation milk yield per milking cow, the parities of unit (1 kg) sale price of raw milk to unit (1 kg) cost of concentrate feed (M/F-parity) (current unit cost of concentrate feed was assumed as to be 1.00 Turkish Lira (TL) were calculated to make BCR that is one of the financial evaluation criteria for the investment projects, as to be 1.00. Calculations showed decreasing each 1% of the real interest rate in Turkey, increasing each 5% of calving rate and increasing each 1000 kg of mean lactation milk yield per milking cow had, separately, about 5-12% positive effect on the parity of unit (1 kg) sale price of raw milk to unit (1 kg) cost of concentrate feed.